A Systematic Review of the Diverse Applications of Alfalfa and Its Role in Sustainable Agriculture - Adil, Muhammad; Shoukat, Usama; Daud, Muhammad; Gul, Isma; Afzal, Rifqa; Aqib, Muhammad; Shafeeq, Sajjad (New Countryside, 2026)
This comprehensive review synthesizes literature from scientific databases, including ScienceDirect, SpringerLink, and Google Scholar, to critically assess the diverse applications of alfalfa (lucerne; Medicago sativa L.). Renowned as a premier forage crop for silage, hay, and grazing, alfalfa delivers exceptional nutritional quality for ruminants, being rich in proteins, vitamins, minerals, and carbohydrates. Beyond its traditional role in animal nutrition, alfalfa is increasingly recognized as a potential functional vegetable for human consumption, with significant medicinal properties, including validated cholesterol-lowering and antidiabetic effects attributed to its bioactive phytochemicals such as saponins and flavonoids. The crop also demonstrates considerable promise for environmental remediation, utilizing its deep root system and high biomass to stabilize heavy metals like cadmium and copper while degrading organic pollutants through phytoremediation mechanisms. Additionally, alfalfa offers viable applications in biofuel and fiber production. Its cultivation is integral to organic and sustainable farming systems, providing critical ecosystem services such as enhancing soil fertility, sequestering carbon, promoting biological nitrogen fixation, and supporting agricultural biodiversity including pollinators, beneficial insects, and avian species of conservation concern. By integrating these nutritional, medicinal, environmental, and agronomic dimensions, this paper consolidates current knowledge to highlight alfalfa’s integral role in promoting resilient and sustainable agricultural systems while addressing interconnected global challenges related to food security, climate change mitigation, and environmental health.